Halal E-commerce: Concept and Implementation in the Food and Beverage Industry - Ramadhan, Zulfikar; Purborini, Vivi Sylvia (Civiliza Publishing, 2024)
e-commerce has greatly expanded its application and scope. More traditional industries have now been incorporated into e-commerce, a significant one of which, in terms of product categories, includes the halal industry. This research uses literature studies, which include literature studies related to the concept of halal in Islam. Literature study on the principles of muamalah in Islam. Literature review about e-commerce and its development in Indonesia. One of the key areas under the halal definition is the treatment of food, food ingredients, and the method of processing. The development of a food and beverage market for Muslims generates interest from a technical point of view, as the aspect of halal must be adhered to. The halal market for Muslims is expanding day by day, in large part due to the spread of Islam in different societies and countries.